Effects of pelleting and dietary fat and fiber levels on pig growth and fat quality - Nemechek, Jeremiah Eugene (Kansas State University, 2014)
In 11 experiments, 7,325 pigs were used to determine the effects of: 1) diet type and form on finishing pig growth performance and carcass fat iodine value (IV); 2) pellet quality and feeder adjustment on pig growth performance; 3) corn particle size and diet form on finishing pig growth performance and carcass characteristics; and 4) dietary acidification, diet complexity, and feed-grade antibiotics on nursery pig growth performance. Feeding diets with wheat middlings and dried distillers grains with solubles all the way until marketing decreased G:F and carcass yield, and worsened carcass fat IV. Withdrawing these ingredients 17 d prior to market restored carcass yield, but resulted in small improvements in IV. Pelleting diets improved growth performance; however, a novel finding is that pelleting diets fed to finishing pigs increased belly fat IV. Feeding nursery pigs from a wide feeder gap may improve ADG and ADFI, with no negative effects on G:F. For finishing pigs, reducing feeder gap reduced feed disappearance and improved G:F. In all experiments, feeding pelleted diets improved G:F, but the greatest improvements occurred when the percentage of fines was minimized. Grinding corn finer than 650 microns decreased ADFI and improved G:F for finishing pigs fed meal diets, but not for pigs fed pelleted diets. Pelleting diets improved ADG and G:F, but the greatest magnitude of G:F improvement to pellets occurred when pigs were fed diets containing the largest particle size corn. Thus, grinding corn finer than 650 microns improved feed efficiency for finishing pigs fed meal diets, but provided no additional benefit for pigs fed pelleted diets. When dietary supplementation of benzoic acid was evaluated, added benzoic acid in nursery pig diets did not influence growth performance in university conditions, whereas feeding complex diets or antimicrobials improved growth. In the commercial setting, acidifiers improved growth in one experiment but not the other. The varying response to acidifiers is likely influenced by health status, age, or starting weight of pigs.
Keywords: Pig; Growth; Iodine value; Pellet; Dietary fiber; Dietary Fat; Animal Sciences (0475)